2015
DOI: 10.1136/sextrans-2015-052214
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the proportion of symptomatic gonococcal, chlamydial and non-gonococcal non-chlamydial urethritis attributable to oral sex among men who have sex with men: a case–control study

Abstract: Background Sexually transmitted infections of the pharynx are common among men who have sex with men (MSM); the degree to which these infections are transmitted through oral sex is unknown. Methods We conducted a case-control study of MSM attending Public Health – Seattle & King County STD Clinic between 2001 – 2013 to estimate the proportion of symptomatic urethritis cases attributable to oral sex using two methods. First, we categorized men into the following mutually exclusive behavioural categories based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 14 publications
2
43
0
2
Order By: Relevance
“…Similarly, there were only two partnerships in which both men had rectal chlamydia in the absence of either man having urethral chlamydia (Additional file 1: Table S1b), which suggests that rectum-to-rectum transmission is also uncommon. These findings also support the notion that pharyngeal-to-urethra and pharynx-to-rectum for chlamydia transmission is likely to be uncommon [15, 16]. …”
Section: Discussionsupporting
confidence: 84%
“…Similarly, there were only two partnerships in which both men had rectal chlamydia in the absence of either man having urethral chlamydia (Additional file 1: Table S1b), which suggests that rectum-to-rectum transmission is also uncommon. These findings also support the notion that pharyngeal-to-urethra and pharynx-to-rectum for chlamydia transmission is likely to be uncommon [15, 16]. …”
Section: Discussionsupporting
confidence: 84%
“…A cross-sectional study has shown 34% of MSM with urethral gonorrhoea had no insertive anal sex or no unprotected insertive anal sex in the previous 3 months, suggests penile-anal sex may not be the only driver for gonorrhoea 20. Very similar results were reported from a case–control study from Seattle where 34% of urethral gonorrhoea was attributable to oral sex 21. These data are supported by a mathematical model showing gonorrhoea in MSM cannot be eliminated even with 100% of condom use for penile-anal sex 17…”
Section: Discussionmentioning
confidence: 57%
“…This could have led to a degree of bias in those who acquired gonorrhoea from oral sex only and had otherwise adopted safe sex practices as around 33% of gonorrhoea is transmitted from unsafe oral sex. 13 The majority of individuals approached for this study agreed to participate but two, who had more chaotic lifestyles and repeat infections, did not attend clinic or declined to participate.…”
Section: Discussionmentioning
confidence: 99%